The Role of Hyperthermia in Methamphetamine-Induced Depression-Like Behaviors: Protective Effects of Coral Calcium Hydride - Wang, Xintao; Tong, Bonan; Hui, Rongji; Hou, Congcong; Zhang, Zilu; Zhang, Ludi; Xie, Bing; Ni, Zhiyu; Cong, Bin; Ma, Chunling; Wen, Di (Frontiers in Molecular Neuroscience, 2022)
Methamphetamine (METH) abuse causes irreversible damage to the central nervous system and leads to psychiatric symptoms including depression. Notably, METH-induced hyperthermia is a crucial factor in the development of these symptoms, as it aggravates METH-induced neurotoxicity. However, the role of hyperthermia in METH-induced depression-like behaviors needs to be clarified. In the present study, we treated mice with different doses of METH under normal (NAT) or high ambient temperatures (HAT). We found that HAT promoted hyperthermia after METH treatment and played a key role in METH-induced depression-like behaviors in mice. Intriguingly, chronic METH exposure (10 mg/kg, 7 or 14 days) or administration of an escalating-dose (2 15 mg/kg, 3 days) of METH under NAT failed to induce depression-like behaviors. However, HAT aggravated METH-induced damage of hippocampal synaptic plasticity, reaction to oxidative stress, and neuroinflammation. Molecular hydrogen acts as an antioxidant and anti-inflammatory agent and has been shown to have preventive and therapeutic applicability in a wide range of diseases. Coral calcium hydride (CCH) is a newly identified hydrogen-rich powder which produces hydrogen gas gradually when exposed to water. Herein, we found that CCH pretreatment significantly attenuated METH-induced hyperthermia, and administration of CCH after METH exposure also inhibited METH-induced depression-like behaviors and reduced the hippocampal synaptic plasticity damage. Moreover, CCH effectively reduced the activity of lactate dehydrogenase and decreased malondialdehyde, TNF- and IL-6 generation in hippocampus. These results suggest that CCH is an efficient hydrogen-rich agent, which has a potential therapeutic applicability in the treatment of METH abusers.